FORM: Submission of IR UMPSA - Noorul Farina, Arifin (Unit Pengurusan Ilmu, Perpustakaan Universiti Malaysia Pahang, 2019)
SUBMISSION INFORMATION 1. UMPSA postgraduate students should submit full text of paper with IR UMPSA submission form and may be email to umplibrary@ump.edu.my. 2. IR UMPSA team will respond the email within 5 working days. 3. IR UMPSA Item ID is a system-generated unique ID and it is automatically generate once an item is deposited into UMPSA-IR. Please specify the IR UMPSA Item ID in any form that require a IR UMPSA Item ID (Proof of publication: IPS, cendekia bitara etc) e.g: URI: http://umpir.ump.edu.my/id/eprint/24884 --- 24884 is IR UMPSA Item ID